Chehalis Stories - Boas, Franz, 1858-1942; Amrine Goertz, Jolynn (Book collections on Project MUSE., 2018)
"Jolynn Amrine Goertz and the Confederated Tribes of the Chehalis Reservation examine the methodologies, shortcomings, and limitations of anthropologists' relationship with Chehalis people in Western Washington and present complementary approaches to field work and its contextualization"--Provided by publisher.